2003
DOI: 10.1065/espr2002.09.133
|View full text |Cite
|
Sign up to set email alerts
|

Emission of biocides from treated materials test procedures for water and air

Abstract: Methods for the determination of biocide emissions from treated materials into water and air were developed and tested in order to support a comparative ecological assessment of biocidal products. Leaching tests, experiments with simulated rain, extraction cleaning of carpets and emission chamber tests were performed with a series of treated materials. The experiments focused on the effect of changes in the procedure as well as characteristics of the specimens and demonstrate the suitability of the proposed me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…Soil water was obtained by passing deionized water at a flow of 27 ml/h through a soil column of 5.9-cm internal diameter and 8.5-cm length during 24 h. The characteristics of leaching solutions are shown in Table 1. Based on a recent literature survey [32], the pH values of these leaching media (between pH 5.86 and 7.23) were not considered to affect the emission rate of metals.…”
Section: Methodsmentioning
confidence: 99%
“…Soil water was obtained by passing deionized water at a flow of 27 ml/h through a soil column of 5.9-cm internal diameter and 8.5-cm length during 24 h. The characteristics of leaching solutions are shown in Table 1. Based on a recent literature survey [32], the pH values of these leaching media (between pH 5.86 and 7.23) were not considered to affect the emission rate of metals.…”
Section: Methodsmentioning
confidence: 99%
“…Diuron, terbutryn and carbendazim used in paints and plaster of facades were detected in effluents of waste water treatment plants (WWTPs) (Gerecke et al, 2002). Nevertheless, most information on the leaching of biocides from facades and plastic roofs is based on laboratory studies (Cadmus and Brophy, 1982;Lindner, 1997;Schoknecht et al, 2003). Elution of mecoprop from bitumen roofs and its transfer to surface water has been reported almost ten years ago (Bucheli et al, 1998).…”
Section: Introductionmentioning
confidence: 95%
“…Hence, the total content of biocides in render and exterior paints ranges from 5 to 10 g kg À1 (Burkhardt et al, 2011). Laboratory studies on constantly soaked material, dipping experiments with alternating wet and dry cycles, or forced rain experiments showed that the biocides leach out of the render material in considerable fractions (Schoknecht et al, 2003;Burkhardt et al, 2007;Schoknecht et al, 2009;Burkhardt et al, 2011Burkhardt et al, , 2012Wangler et al, 2012). The leaching process of biocides from render is assumed to be a multistep process: (1) removal from the surface layer which is itself (2) in equilibrium with the deeper layers of the render, from which (3) the surface layer is constantly refilled.…”
Section: Introductionmentioning
confidence: 98%